The activation of the Arabidopsis P-ATPase 1 by the brassinosteroid receptor BRI1 is independent of threonine 948 phosphorylation - Witthöft, Janika (Landes Bioscience, 2011)
The plasma membrane-spanning receptor brassinosteroid insenstive 1 (BRI1) rapidly induces plant cell wall expansion in response to brassinosteroids such as brassinolide (BL). Wall expansion is accompanied by a rapid hyperpolarization of the plasma membrane, which is recordable by measuring the fluorescence lifetime (FLT) of the green fluorescent protein (GFP) fused to BRI1. For the BL induction of hyperpolarization and wall expansion, the activation of the plasma membrane P-type H(+)-ATPase is necessary. Furthermore, the activation of the P-ATPase requires BRI1 kinase activity and appears to be mediated by a BL-modulated association of BRI1 with the proton pump. Here, we show that BRI1 also associates with a mutant version of the Arabidopsis P-ATPase 1 (AHA1) characterized by an exchange of a well-known regulatory threonine for a non-phosphorylatable residue in the auto-inhibitory C-terminal domain. Even more important, BRI1 is still able to activate this AHA1 mutant in response to BL. This suggests a novel mechanism for the enzymatic activation of the P-ATPase by BRI1 in the plasma membrane. Furthermore, we demonstrate that the FLT of BRI1-GFP can be used as a non-invasive probe to analyze long-distance BL signaling in Arabidopsis seedlings.